2015
DOI: 10.1590/0103-8478cr20131232
|View full text |Cite
|
Sign up to set email alerts
|

Perdas de nitrogênio do solo e resposta do pessegueiro à adição de composto orgânico

Abstract: RESUMO A aplicação de composto orgânico no solo pode incrementar a produção de pêssego, porém parte do N pode ser perdido por lixiviação e volatilização. O trabalho objetivou avaliar o estado nutricional das plantas, a produção de pêssego, a lixiviação de formas de N no solo e a volatilização de N-NH Palavras-chave: resíduo orgânico, N mineral, Prunus persica. ABSTRACT The application of organic compost to the soil can increase the production of peach, although part of the N may be lost by leaching and volatil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 14 publications
1
5
0
3
Order By: Relevance
“…In the following year, the plants that received N, regardless of the dose (100 or 200 kg ha -1 of N) differed from the zero dose, presenting the highest levels of leaf N. And agreeing with the results obtained by Dolinski et al (2005), and Brunetto et al (2007). However, the levels were below normal, as established by the RS / SC (2016) Soil Chemistry and Fertility Commission, reinforcing the hypothesis that there may have been an underdosing of N. The K levels were not affected, unlike the observed by Sete et al (2015), which verified a quadratic increase of K with the increase of the dose of organic compound produced from waste from juice industries, poultry slaughtering and sawdust. This increase of K may have occurred due to the fact that the nutrient is found in part in the free form in the residue, different from the present work in which the K was not supplied to the plants.…”
Section: Fertilizer Maintenance Nitrogen In Vegetative Development Ansupporting
confidence: 83%
“…In the following year, the plants that received N, regardless of the dose (100 or 200 kg ha -1 of N) differed from the zero dose, presenting the highest levels of leaf N. And agreeing with the results obtained by Dolinski et al (2005), and Brunetto et al (2007). However, the levels were below normal, as established by the RS / SC (2016) Soil Chemistry and Fertility Commission, reinforcing the hypothesis that there may have been an underdosing of N. The K levels were not affected, unlike the observed by Sete et al (2015), which verified a quadratic increase of K with the increase of the dose of organic compound produced from waste from juice industries, poultry slaughtering and sawdust. This increase of K may have occurred due to the fact that the nutrient is found in part in the free form in the residue, different from the present work in which the K was not supplied to the plants.…”
Section: Fertilizer Maintenance Nitrogen In Vegetative Development Ansupporting
confidence: 83%
“…Similar results were obtained by Guarçoni & Ventura (2011), who reported that the increase of the N amount led to an increase of leaf length. According to Medeiros et al (2004), the addition of N promotes cell division, and it is involved in growth and development (Oliveira et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…There is no guidance regarding N dose that should be applied in an orchard with a higher density of plants. According to Sete et al (2015), the N accumulated in the plants throughout crop seasons contributes to increase peach tree yield.…”
Section: Introductionmentioning
confidence: 99%
“…Agrar., v. 58, n. 3, p. 257-262, jul./set. 2015 disponibilidade de formas de N mineral, como N-NO 3 e N-NH 4 + (Sete et al, 2015). O N quando absorvido em quantidades acima da demanda da planta pode estimular o vigor da parte aérea, diminuindo a incidência de raios solares no interior do dossel, a circulação de ar e, consequentemente, potencializar a ocorrência de doenças fúngicas nas folhas e também reduzir a taxa de fecundação das flores (Duchêne et al, 2001).…”
Section: Resultsunclassified